The influence of surface tension on wetting in dampening solution and sustainability of printing: A review - Cem Aydemir; Semiha Yenidoğan (Journal of Graphic Engineering and Design, 2019)
Offset is defined as a printing technique using a system of two-fluids (ink + dampening solution) that requires a constant monitoring and a balancing system due to the physical-chemical features of the process. Ink and dampening solution on the printing plate surface should not be intergraded during the chemical interaction. Image and non-image areas on the plate surface can be separated from each other only through the interaction of dampening solution and ink. The dampening solution is responsible for the wetting of non-image areas on a printing plate, and are applied to the entire plate. In the wetting process, the amount of the dampening solution on the plate should be at the lowest level. This can be provided only by lowering the surface tension of the dampening solution. Thus, quality printing results, such as edge sharpness, high color intensity and high print gloss are achieved with a small amount of wetting on the printing plate surface. In this study, the wetting of the printing plate surface is investigated under the effects of surface tension of dampening solution and its angle of contact with the printing plate and current studies related to the subject are reviewed and discussed.